The Effect of Population, Open Unemployment Rate and Poverty Rate on the Economic Growth of East Nusa Tenggara - Utami, Meilasari Sri; Huda, Syamsul (Indonesian Journal Publisher, 2025)
The low rate of economic growth in East Nusa Tenggara (NTT), coupled with high levels of poverty, unemployment, and population growth, forms the main basis of this study. The objective is to examine the influence of population size, open unemployment rate, and poverty level on regional economic growth over the period 2004 to 2023. This research applies a quantitative approach utilizing multiple linear regression analysis. The data used are secondary data obtained from official publications of the Central Bureau of Statistics (BPS), including East Nusa Tenggara in Figures and socio-economic reports. The results indicate that population size and open unemployment significantly and negatively affect economic growth, while poverty level has a negative but statistically insignificant effect. These findings imply that population and unemployment growth, without being accompanied by improvements in employment opportunities and regional development equity, tend to hinder economic performance. Hence, development policies need to be more focused on human resource enhancement, local economic sector strengthening, and employment expansion to achieve more inclusive and sustainable economic progress in NTT.